Сучасний стан та тенденції освітньої міграції - Марценко, Наталія; Martsenko, Nataliia (ЗУНУ, 2020)
Проаналізовано поняття, сутність та сучасний стан освітньої міграції. Проведено характеристику нормативно-правового регулювання освітньої міграції. Акцентовано увагу на актуальній тенденції до суттєвого зростання кількості українських студентів, що навчаються за кордоном. Проаналізовано мотиви виїзду молоді за кордон з метою здобуття освіти, серед яких виокремлено якість освіти, можливість безкоштовного навчання, можливість отримання стипендій та грантів на навчання, порівняно прості умови вступу, кращі можливості щодо працевлаштування тощо. Досліджено вплив карантинних обмежень на освітні міграційні процеси та розглянуто шляхи подолання кризи. Наголошено на доцільності постійного удосконалення освітнього процесу в напрямку розвитку науки та технологій задля підтримки конкурентоспроможності університету Relevance of the research topic. Educational migration is of great importance not only at the local level (at the university level), as it allows to attract as many students as possible, but also at the global level (at the level of the state educational policy). Today, many countries consider educational migration as an element of their foreign policy, which aims to strengthen economic, cultural and political influence in the world. Moreover, the provision of educational services is becoming an important export, cost-effective for the education sector. At the same time, educational migration affects not only economic income, but also the improvement of demographic and labor structure of society through the influx of educated young people of reproductive age, obtaining new citizens who are integrated into society through the education system and more. Therefore, educational migration continues to play an important role in the socio-economic development of countries, identifying trends in education (the most popular specialties, competitive universities) and does not lose its relevance. The purpose of this study. In this article we will try to analyze the concepts and features of educational migration. In addition, we will consider the state of educational migration in the context of distance learning during the introduction of quarantine restrictions associated with COVID-19. Results of the research. The influence of quarantine restrictions on educational migration processes is studied and the ways of overcoming the crisis are considered. The paper emphasizes the expediency of continuous improvement of the educational process in the direction of development of science and technology to maintain the competitiveness of the university.
Current state and trends of educational migration
Keywords: освітня міграція; міграційні процеси; еміграція; імміграція; дистанційна освіта; educational migration; migration processes; emigration; immigration; distance education